Chronic and low exposure to a pharmaceutical cocktail induces mitochondrial dysfunction in liver and hyperglycemia: Differential responses between lean and obese mice. Issue 4 (8th August 2016) - Buron, Nelly; Porceddu, Mathieu; Roussel, Célestin; Begriche, Karima; Trak‐Smayra, Viviane; Gicquel, Thomas; Fromenty, Bernard; Borgne‐Sanchez, Annie
ABSTRACT: Pharmaceuticals are found in the environment but the impact of this contamination on human and animal health is poorly known. The liver could be particularly targeted since a significant number of these drugs are hepatotoxic, in particular via oxidative stress and mitochondrial dysfunction. Notably, the latter events can also be observed in liver diseases linked to obesity, so that the obese liver might be more sensitive to drug toxicity. In this study, we determined the effects of a chronic exposure to low doses of pharmaceuticals in wild‐type and obese mice, with a particular focus on mitochondrial function. To this end, wild‐type and ob/ob mice were exposed for 4 months to a cocktail of 11 pharmaceuticals provided in drinking water containing 0.01, 0.1, or 1 mg/L of each drug. At the end of the treatment, liver mitochondria were isolated and different parameters were measured. Chronic exposure to the pharmaceuticals reduced mitochondrial respiration driven by succinate and palmitoyl‐l ‐carnitine in wild‐type mice and increased antimycin‐induced ROS production in ob/ob mice. Hyperglycemia and hepatic histological abnormalities were also observed in treated ob/ob mice. Investigations were also carried out in isolated liver mitochondria incubated with the mixture, or with each individual drug. The mitochondrial effects of the mixture were different from those observed in treated mice and could not be predicted from the results obtained with each drug. Because some of the 11 drugs included in our cocktail can be found in water at relatively high concentrations, our data could be relevant in environmental toxicology. © 2016 Wiley Periodicals, Inc. Environ Toxicol 32: 1375–1389, 2017.